The book of scandal - London, Julia (London, Julia. Scandalous series., 2023)
"Known as the Libertine of Lindsey, Nathan Grey, the Earl of Lindsey, is notorious for his disgraceful ways with women. But when he hears rumors that his estranged wife, Evelyn, is about to be named in the Princess of Wales's infamous Book of Scandal, he has no choice but to remove her from London to protect them both--even if it's against her wishes. Evelyn has no affection for the man who broke her heart years ago, but she is also no longer the na̐ve young girl he married. Her reluctant reunion with Nathan quickly turns into a battle of wills that lays bare the passion that still burns between then. But the two have powerful adversaries who would like nothing more than to see them torn apart and soon, Nathan must do everything he can to prove to the world and to Evelyn that she is not only his wife, but the woman he loves"--Page 4 of cover.